Pengaruh green innovation, green organizational culture, dan environmental leadership terhadap green competitive advantage pada UMKM - Wiratri, Rafika Hana; Hadi, Syamsul; Purnamarini, Tri Ratna (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study was conduct to analys theinfluence of Green Inovation, Green Organization Culture, and Environmental Leadership on Green Competitive Advantage in MSMEs in Giriloyo Batik Village, Bantul. The research method used was a quantitative method with a non-probability sampling technique, namely saturated or census sampling. There were 60 respondents who were managers of Giriloyo Batik Village MSMEs in Bantul. The data colection method use was a questionaire constructed based on previous research with 28 statement items in the form of a1-5 Likert scale, then the data was analyzed using SmartPLS version 4.1.1.5. The result of the study show that the three independen variables have a positif and significant effect on the dependent variable. This means that Green Innovation, Green Organizational Culture, and Environmental Leadership are variables that can strengthen the formation of GreenCompetitive Advantage in Giriloyo Batik Village MSMEs in Bantul. The findings of this study are expect to contributed to the development oftheoretical literatur on Human Resource Management (HRM) and have practical implications for MSMEs in developing sustainable business strategies.